The fortuitous teacher : a guide to successful one-shot library instruction - Cisse, Sarah (Chandos information professional series., 2016)
This book discusses how librarians have become accidental teachers in the academic university setting. It explains how librarians are prepared by MILS programs to teach, compares typical characteristics of teachers versus librarians, and presents tactics on how to learn effective teaching skills on the job.